Association between disability, social support and depressive symptoms in Chinese older adults: A national study - Tian, Gang; Li, Rui; Cui, Yiran; Zhou, Tong; Shi, Yan; Yang, Wenyan; Ma, Yulan; Shuai, Jingliang; Yan, Yan (Frontiers in Public Health, 2022)
Objective: Activities of daily living(ADL) and social support can impact depressive symptoms of the elderly. Yet, studies infrequently discuss the moderating role of social support when evaluating the association between ADL and depressive symptoms. The purpose of this study was to explore the relationship between ADL, social support, and depressive symptoms among the Chinese elderly, and further examine the moderating effect of social support. Materials and Methods: Using the 2018 Chinese Longitudinal Healthy Longevity Survey (CLHLS) data set, we finally selected 9231 Chinese elderly after screening. We used multiple linear regression and moderating model to explore the relationship between ADL, social support, and depressive symptoms. Results: A total of 9231 patients were included in this study, and approximately 26.75% of the elderly had depressive symptoms. Study found that depressive symptoms were associated with social support(=-0.102, 95% CI:-0.143–0.060), B-ADL(=0.296, 95%CI:0.248-0.343), and I-ADL(=0.174, 95% CI:0.152-0.195). Moreover, the result also showed that social support moderated the effects of B-ADL(B-ADL*social support=0.034, 95% CI:0.014- 0.053) and I-ADL( I-ADL*social support=0.025, 95% CI:0.017-0.033)on depressive symptoms. Conclusions: The study suggests that ADL and social support can affect depressive symptoms, and social support moderates the effect of ADL on depressive symptoms. Therefore, taking effective measures to reduce the elderly disability rate of ADL and increase their social support are a necessary condition for realizing mental health.